Criminal Protection from Misleading Voters : A Case Study on the Parliamentary Elections in the Kingdom of Bahrain - AlShamlan, Noora (Journal of Legal Sciences, 2023)
Elections are one of the pillars of democracy. Therefore, adequate legal guarantees must exist to preserve democracy. One of the most important aspects is setting rules to govern electoral campaigning, due to its impact on the choice of the electorate, and thus the formation of the parliament, legislation, and state policy for several years. This study focuses on the candidates’ behavior that might mislead voters and affect their choices, which include election promises whether directly or indirectly. The study will focus on examining the limits of electoral promises and their mandatory extent to achieve criminal protection for the voters. This study will adopt the comparative analysis, and descriptive approach to present its hypotheses by examining Bahraini legislation and comparative legislation and judiciary.The study resulted in drawing the objective boundaries for electoral promises, and the actions of the members of the parliament, which is considered misleading. Moreover, proposing legal articles and amendments to provide further legal criminal in the Kingdom of Bahrain.